Quality of “Cripps Pink” apples following the application of 1-MCP, ethanol vapor and nitric oxide as pretreatments for controlled atmosphere storage - Soardi K.* (2022)
© 2021 Wiley Periodicals LLC.The objective of this work was to evaluate the effect of the application of technologies complementary to controlled atmosphere (CA) storage, 1-methylcyclopropene (1-MCP), ethanol vapor (Eth), and nitric oxide (NO), on the quality of “Cripps Pink” apples. The treatments evaluated were control (without complementary technology), 1-MCP (1 μl L−1), Eth (6 ml/kg), and NO (10 and 20 μl L−1), applied before the fruits were stored in a CA (1.2 kPa O2 + <0.1 kPa CO2 at 1.5 ± 0.2°C and 94 ± 2% RH). Fruit treated with 1-MCP showed lower respiration and ethylene production rates, superficial scald and mealy fruit, greener peel and higher flesh firmness, and titratable acidity. All treatments additional to CA led to a lower respiratory rate and higher total phenolic compound content and total antioxidant activity than the control. NO (10 and 20 µl L−1) treatment prior to CA storage reduced the respiratory rate and superficial scald compared to the control. Practical application: This study analyzed the effects of pretreatment with 1-methylcyclopropene (1-MCP), ethanol vapor, and NO fumigation before controlled atmosphere storage of “Cripps Pink” apples as a way to preserve fruit quality. 1-MCP treatment maintained better quality than the other treatments. NO treatment showed intermediate results of quality maintenance because reduced superficial scald and resulted in the highest total phenolic compound content and antioxidant activity in organic “Cripps Pink” apple.